Interaction between the Linear and Nonlinear Polarization in Optical Fibre - Kuja, S.; Kipnoo, Rotich E.K.; Boiyo, Kiboi; Waswa, D.; Amolo, G.; Muguro, K. M. (My University, 2014)
Interaction between polarization mode dispersion (PMD) and nonlinear induced birefringence in a fibre with consideration of mode coupling has been investigated theoretically using Matlab and Optism. The investigations show that PMD leads to a distortion of the signal but when it is frequency independent, its overall effect is just a rotation of the signal state of polarization (SOP) on the Poincare sphere. Further investigation show that the effect of nonlinear birefringence alone depolarizes the signal, while in high PMD links where polarization mode coupling is high, the nonlinear birefringence effect couples with second-order PMD such that it may reduce the penalty and improve the signal DOP. It is also found that when nonlinear birefringence becomes significant, asymmetry arises between the two principal axes of the fibre, such that it is only one axis which experiences the effect of nonlinear birefringence.
Keywords: PMD; Nonlinear birefringence; DOP; Polarization mode coupling.